Health risk assessment of potentially toxic elements in the dry deposition fraction of settleable particulate matter in urban and suburban locations in the city of Gijón, Spain. Issue 6 (December 2021) - Lara, Rosa; Suárez-Peña, Beatriz; Megido, Laura; Negral, Luis; Rodríguez-Iglesias, Jesús; Fernández-Nava, Yolanda; Castrillón, Leonor
Abstract: This study investigates the human health risk of Al, As, Fe, Mn, Ni, Pb, Sb and Sr in the dry deposition fraction of settleable particulate matter (DSPM). Sixty samples were collected at an industrial suburban site ('EMA') and a waterfront urban site ('Naval') in Gijón, a coastal city in northern Spain. Up to 4898.4 mg m −2 d −1 were measured at the station closer to industrial activity. The levels of the eight elements were greater at this site. Fe and Al were the major constituents, comprising up to 50% of DSPM. The human health risk posed by DSPM was assessed using a U.S.EPA methodology. The level of exposure to the metals/metalloids in this atmospheric pollutant was studied via ingestion, inhalation, and dermal contact. The results showed that ingestion was the main exposure pathway for the residents at the two locations, followed by dermal contact and inhalation. For adults, the non-carcinogenic hazard indexes and the carcinogenic risk levels of the eight elements were within the acceptable levels (1 and 10 −5, respectively). Nevertheless, in the case of children, the non-carcinogenic hazard indexes of Fe and Pb as well as the carcinogenic risk level of As via ingestion were higher than those thresholds. Despite its importance, little research has focused on assessing the human risk posed by metals/metalloids in DSPM. Although there are uncertainties regarding the exposure factors and toxicity values, the outcomes of this study provide useful knowledge for regulatory authorities to establish appropriate mitigation measures to reduce DSPM emissions in urban and suburban environments. Graphical Abstract: ga1 Highlights: Human health risk posed by dry deposition was compared at urban and suburban sites. The closer to industries, the higher the levels of Al, As, Fe, Mn, Ni, Pb, Sb and Sr. Ingestion pathway implied the greatest potential risks for both adults and children. Fe and Pb exceeded the tolerable non-cancer risk threshold for children via ingestion. Cancer risk indicators revealed that As via ingestion posed a threat to children.